Early detection of subclinical rheumatic heart disease through echocardiographic screening: a study in North Sumatra, Indonesia - Ardini, Tengku Winda; Ilyas, Kamal Kharazzi; Nasution, Ali Nafiah; Ketaren, Andre Pasha; Napitupulu, Bertha Gabriella; Batubara, Gio Justisia; Sarastri, Yuke; Raynaldo, Abdul Halim; Siregar, Abdullah Afif; Siregar, Yasmine Fitrina; Dewita, Auliya; Andra, Cut Aryfa; Lubis, Anggia Chairuddin (Heart Science Journal, 2024)
BACKGROUND: Given the urgent need to address the significant morbidity and mortality associated with Rheumatic Heart Disease (RHD) in Indonesia, there is a growing interest in exploring cost-effective screening approaches, such as handheld echocardiography.OBJECTIVES: The purpose of this study was to ascertain the prevalence of RHD in North Sumatra, Indonesia.METHODS: This descriptive observational study was conducted within the population of North Sumatra from 2022 to 2023. Junior high school students aged 12 to 15 years were included from randomly selected schools in Langkat, Tebing Tinggi, and Labuhan Batu. Data collection encompassed various parameters, including social demographic information, parental characteristics, environmental factors, household details, anthropometric measurements, physical assessments, auscultation findings, and echocardiographic data. The data were analyzed descriptively.RESULTS: In our study, a total of 692 children were examined, with an average age of 12.9 years and a standard deviation of 1.1 years, among whom 42.5% were male. Utilizing echocardiographic evaluations, we identified RHD in four children, yielding a prevalence rate of 0.6%. Further examination of these cases revealed that the majority, accounting for three individuals (75%), exhibited borderline RHD, while one child (25%) presented with definite RHD.CONCLUSION: In our study population, the prevalence of RHD was 0.6%. A broader echocardiographic screening program is necessary to determine the overall prevalence of RHD, assess the disease burden, and identify individuals earlier to prevent adverse outcomes.